2022
DOI: 10.21511/ee.13(1).2022.08
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the economic impact of carbon emissions in Africa

Abstract: The economic impact of carbon emissions in Africa is gaining traction in the extant literature. This study adopted Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to concomitantly track data on carbon emissions versus economic growth in Africa from 2018 to 2022 providing evidence from a meta-analysis. Through database searches, 591 publications were identified. A machine learning algorithm called Latent Dirichlet Allocation (LDA) was used as a visualization technique for reporting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…An important fact when conducting bathymetric measurements are also the parameters of the echo sounder, such as the operating temperature range, the width of the trace of a single beam, the so-called footprint, the number of beams (the number of which can vary from several dozen to several hundred), and the angle of the strip [38]. The smaller the footprint and the greater the number of beams, the more accurate the measurements.…”
Section: Multibeam Echo Sounder Depth Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…An important fact when conducting bathymetric measurements are also the parameters of the echo sounder, such as the operating temperature range, the width of the trace of a single beam, the so-called footprint, the number of beams (the number of which can vary from several dozen to several hundred), and the angle of the strip [38]. The smaller the footprint and the greater the number of beams, the more accurate the measurements.…”
Section: Multibeam Echo Sounder Depth Testingmentioning
confidence: 99%
“…The larger angle of the search lane increases the speed of measurement generation by reducing the number of individual passes per measurement unit, but it may also reduce the accuracy of measurements due to large deviations and uncertainties on the outer beams. Therefore, it is important to use the so-called overlap [38,39].…”
Section: Multibeam Echo Sounder Depth Testingmentioning
confidence: 99%
“…Recently, electric mobility and the deployment of electric freight transport have become one of the key priorities of transforming transport solutions on the path to sustainable economic development and reducing environmental hazards. One of the main objectives of distribution logistics is to deliver goods at the required time and to the required quality while maximizing vehicle utilization and reducing the negative impact on the environment by reducing CO 2 emissions (Rajkoomar et al, 2022;Li & Zhou, 2021). With the development of alternative powertrains for passenger vehicles, especially in the field of electric power, it is possible to consider applications in freight transport, specifically for distribution logistics and urban logistics (Kozlovskyi et al, 2019;Strielkowski et al, 2019;Pan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cantelmo et al (2019) found that more frequent and severe weather disasters in these countries caused an average loss of well-being equivalent to a steady 1.6 percent reduction in consumption. Based on the analysis of systematic reviews and meta-analyses (PRISMA), Rajkoomar et al (2022) and Supriyanto et al (2022) substantiate that economic growth has a negative and significant effect on carbon emissions in Africa. At the same time, the most vulnerable countries to the impacts of climate change have a high level of corruption, which defines the relevance of research and the increased attention of the international community to the effective use of financial support aimed at climate goals.…”
Section: Introductionmentioning
confidence: 99%